Terahertz radiation enhancement in dipole photoconductive antenna on LT-GaAs using a gold plasmonic nanodisk array. (December 2019) - Bashirpour, Mohammad; Poursafar, Jafar; Kolahdouz, Mohammadreza; Hajari, Mohsen; Forouzmehr, Matin; Neshat, Mohammad; Hajihoseini, Hamid; Fathipour, Morteza; Kolahdouz, Zahra; Zhang, Guoqi
Highlights: A plasmonic THz PCA consisting Ti/Au nanodisks in the antenna gap is presented. All structural parameters were optimized to reach highest electron-hole generation. The PCA benefits from enhanced quantum efficiency enabled by plasmon excitation. The finalized PCA resulted in more than 5.6 times THz electric field radiation. This THz field enhancement shows a way to improve the optical-to-THz efficiency. Abstract: This study proposes a new-fashioned plasmonic photoconductive antenna (PCA) with high optical-to-terahertz (THz) conversion efficiency. Finite element method was used to investigate and optimize the interaction of 800 nm femtosecond laser with the designed nanodisk array in the antenna's gap using its geometrical parameters. According to the simulation results, our optimized nanoplasmonic structure showed more than 38% enhancement in the absorption efficiency compared to the conventional structure without any nanostructure. Measuring the THz radiation of the fabricated PCAs using a time domain spectroscopy setup exhibited an exceptional 5.6 times higher electric field in 0.1–2.5 THz range compared to a similar PCA but without nanoplasmonic structure.